Genome of an iconic Australian bird: High‐quality assembly and linkage map of the superb fairy‐wren (Malurus cyaneus). (2nd January 2020) - Peñalba, Joshua V.; Deng, Yuan; Fang, Qi; Joseph, Leo; Moritz, Craig; Cockburn, Andrew
Abstract: The superb fairy‐wren, Malurus cyaneus, is one of the most iconic Australian passerine species. This species belongs to an endemic Australasian clade, Meliphagides, which diversified early in the evolution of the oscine passerines. Today, the oscine passerines comprise almost half of all avian species diversity. Despite the rapid increase of available bird genome assemblies, this part of the avian tree has not yet been represented by a high‐quality reference. To rectify that, we present the first high‐quality genome assembly of a Meliphagides representative: the superb fairy‐wren. We combined Illumina shotgun and mate‐pair sequences, PacBio long‐reads, and a genetic linkage map from an intensively sampled pedigree of a wild population to generate this genome assembly. Of the final assembled 1.07‐Gb genome, 975 Mb (90.4%) was anchored onto 25 pseudochromosomes resulting in a final superscaffold N50 of 68.11 Mb. This high‐quality bird genome assembly is one of only a handful which is also accompanied by a genetic map and recombination landscape. In comparison to other pedigree‐based bird genetic maps, we find that the fairy‐wren genetic map more closely resembles those of Taeniopygia guttata and Parus major maps, unlike the Ficedula albicollis map which more closely resembles that of Gallus gallus . Lastly, we also provide a predictive gene and repeat annotation of the genome assembly. This new high‐quality, annotated genome assembly will be an invaluable resource not only regarding the superb fairy‐wren species and relatives but also broadly across the avian tree by providing a novel reference point for comparative genomic analyses.